2015
DOI: 10.1080/00268976.2015.1062151
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of ‘free-standing’ hollow Au nanocages at finite temperatures: a BOMD study

Abstract: Finite-temperature behaviour of a hollow golden cage (HGC) plays a crucialrole in its potential applications as a catalyst, drug delivery agent, contrasting agent and so on. This physico-chemical property of HGCs is not well understood so far. In that context, Born-Oppenheimer molecular dynamics (BOMD) simulations are performed on a well-known 'free-standing' HGC. The cluster considered in this study is the ground state Au 18 cluster (a cage with a diameter of about >5.5Å).The results thus obtained are compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 74 publications
2
4
0
Order By: Relevance
“…It is well known that the Nose ´-Hoover thermostat is superior to the Berendsen thermostat. However, in one of our earlier studies, 36 we have verified the molecular dynamics results obtained by using the two thermostats at lower temperatures and found them to be consistent with each other. The nuclear positions are updated using a velocity Verlet algorithm with a time step of 1 fs.…”
Section: Computational Detailssupporting
confidence: 80%
See 1 more Smart Citation
“…It is well known that the Nose ´-Hoover thermostat is superior to the Berendsen thermostat. However, in one of our earlier studies, 36 we have verified the molecular dynamics results obtained by using the two thermostats at lower temperatures and found them to be consistent with each other. The nuclear positions are updated using a velocity Verlet algorithm with a time step of 1 fs.…”
Section: Computational Detailssupporting
confidence: 80%
“…32 The finite temperature behavior of smaller (n = 3-10) and medium sized (n = 16-20) gold clusters is extensively studied in earlier reports. [33][34][35][36][37] However, systematic ab initio molecular dynamics studies on bigger clusters particularly in the size range of n = 21-30 are very rare. In the same size range, ligand protected clusters have been well explored for clusters such as Au 25 (SR) 18 , 38 Au 28 (SR) 20 , 39 etc.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that Nose-Hoover thermostat is superior to Berendeson's thermostat. However, in one of our earlier studies, 35 we verified that the molecular dynamics results obtained with the two thermostats at lower temperatures were consistent with each other. The nuclear positions were updated using the velocity Verlet algorithm with a time step of 1 fs.…”
Section: Computational Detailssupporting
confidence: 84%
“…To some extent, issues related to thermal stability and finite-temperature behavior have been addressed for pristine or bare gold clusters. However, to the best of our knowledge, there has been no systematic study to evaluate the finite-temperature response of doped gold clusters. Finite-temperature studies on other doped systems such as carbon doping in silicon, , Li doping in aluminum, , Sn doping in lithium, , and C doping in Al/Ga have demonstrated that the addition of an impurity controls the thermal stability of a system, while also imparting a higher catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…A number of such golden fullerenes, that is, I h ‐Au32- , T d ‐ Au16- , C 2 v ‐Au17- and C 2 v ‐Au18- , have been identified by photoelectron spectroscopy by Wang and co‐workers . Since the publication of the paper by Johansson et al., a number of other studies on golden fullerenes have appeared, either with a hollow cage, or with a central metal enclosed extending on the original work of Pyykkö and Runeberg on W@Au 12 . For a recent review see Wang and Wang …”
Section: Introductionmentioning
confidence: 99%